The Influence of Resected Gastric Weight upon Weight Loss after Sleeve Gastrectomy. Issue 12 (December 2015) - Rosas, Ulysses; Hines, Harrison; Rogan, Daniel; Rivas, Homero; Morton, John
Bariatric surgery is an effective and enduring treatment for obesity. Sleeve gastrectomy (SG) has emerged as an increasingly prevalent surgical intervention. Further investigation is required to determine optimal standardization of SG. Data were collected prospectively for 64 patients who underwent a laparoscopic vertical SG between December 2010 and February 2013 at a single academic institution. Demographic, intraoperative, and postoperative (postop) data were collected for all patients including weighing each resected stomach. The total resected gastric weight varied widely. Preoperatively, patients in the upper tercile for resected gastric weight were more likely to be male (lower 10%, middle 23%, upper 52%, P = 0.006) and had greater initial weights (lower 255.9%, middle 245.1%, upper 280.0%, P = 0.019). The resected gastric weight (g) varied by tercile (mean of all, 131.24 ± 39.8; lower, 93.9 ± 10.9; middle, 127.4 ± 11.7; upper 172.7 ± 37.9, P = 0.000). Patients were followed for 1-year postop with follow-up data for 94 per cent (60/64) of participants. Per cent excess weight loss (EWL) was obtained at three, six, and 12 months postop. At 12 months, there was a trend toward increased per cent EWL in the upper tercile (lower 61.1%, middle 54.1%, upper 90.5%, P = 0.057). In conclusion, while the amount of gastric sleeve resected can vary, this study shows that intraoperative assessment of resected sleeve weight can help evaluate adequacy of resection. Improved 12-month per cent EWL in patients with greater resected tissue demonstrate potentially improved outcomes.